Macro : Inflation And Economic Stability In Islam - Siregar, Rahmat Azahar; Abdul Majid, M. Shabri (International Journal of Science, Technology & Management, 2022)
Inflation is a frequent conversation, both in economic meetings and in income-raising talks. Inflation in a country cannot be eliminated, it can only be minimized by indicators held by the government. In this study, it will discuss inflation and economic stability in Islam. This research is a descriptive qualitative research with a Library approach, and is narrated according to the needs of the formulation to be addressed. The results of this study show that the conventional perspective states that the causes of inflation are cost push, demand pull, and mixed (mixed). Meanwhile, the Islamic paradigm emphasizes that inflation is the result of natural error and human error.